Rasionalisme dan Epistemologi: Analisis Kritis atas Pengaruh Rene Descartes terhadap Filsafat Barat - Rijal, Syaiful (Aqlania, 2024)
The emergence of the Renaissance in the Western world started when individuals exhibited a high degree of criticality towards the prevailing circumstances, subjecting everything to empirical scrutiny. To attain a truth, it is necessary to employ several modes of thinking and evidence, one of which is the criterion of rationalism, which significantly shaped the foundation of the Age of Enlightenment. The present evaluation of rationalism in the Postmodern era is crucial to determine if the sole actual truth is a rational truth that is logically coherent, if the ratio is the exclusive source of truth, or if there exist alternative truths that rationalism is unable to attain. This study aims to acquire knowledge and comprehension of the epistemology of rationalism as a theory of truth. This study methodology employs literature (library research) by systematically collecting and tracking data or library resources pertaining to the topic of the discussion and the actual problem. The results indicate that rationalism is a philosophical perspective that asserts reason as the primary instrument for acquiring knowledge, with the ultimate truth being attributed to human reason or rationality. 2) In his philosophy, Descartes introduced a way of scepticism, the doubt method, which involves questioning all beliefs, ideas, thoughts, and materials acquired by the senses. The integrity of information and knowledge acquired by individuals from birth is not assured, necessitating thorough testing through doubt. 3) Despite being driven by rational and empirical principles, rationalism is inherently incapable of elucidating or manifesting empirical existence beyond the confines of the intellect, such as phenomena related to colour, taste, smell, or shadow.